Spectroscopic and Thermooxidative Analysis of Organic Okra Oil and Seeds from Abelmoschus esculentus - Geórgia de Sousa Ferreira Soares; Vinicius de Morais Gomes; Anderson dos Reis Albuquerque; Manoel Barbosa Dantas; Raul Rosenhain; Antônio Gouveia de Souza; Darlene Camati Persunh; Carlos Alberto de Almeida Gadelha; Maria José de Carvalho Costa; Tatiane Santi Gadelha (The Scientific World Journal)
With changes in human consumption from animal fats to vegetable oils, the search for seed types, often from unconventional vegetable sources has grown. Research on the chemical composition of both seed and oil for Brazilian Okra in South America is still incipient. In this study, flour and oil from organic Okra seeds (Abelmoschus esculentus L Moench), grown in northeastern Brazil were analyzed. Similar to Okra varieties from the Middle East and Central America, Brazilian Okra has significant amounts of protein (22.14%), lipids (14.01%), and high amounts of unsaturated lipids (66.32%), especially the oleic (20.38%) and linoleic acids (44.48%). Oil analysis through PDSC revealed an oxidation temperature of 175.2°C, which in combination with low amounts of peroxide, demonstrates its resistance to oxidation and favors its use for human consumption.